An invisible touch: Body-related multisensory conflicts modulate visual consciousness. (29th July 2016) - Salomon, Roy; Galli, Giulia; Łukowska, Marta; Faivre, Nathan; Ruiz, Javier Bello; Blanke, Olaf
Abstract: The majority of scientific studies on consciousness have focused on vision, exploring the cognitive and neural mechanisms of conscious access to visual stimuli. In parallel, studies on bodily consciousness have revealed that bodily (i.e. tactile, proprioceptive, visceral, vestibular) signals are the basis for the sense of self. However, the role of bodily signals in the formation of visual consciousness is not well understood. Here we investigated how body-related visuo-tactile stimulation modulates conscious access to visual stimuli. We used a robotic platform to apply controlled tactile stimulation to the participants' back while they viewed a dot moving either in synchrony or asynchrony with the touch on their back. Critically, the dot was rendered invisible through continuous flash suppression. Manipulating the visual context by presenting the dot moving on either a body form, or a non-bodily object we show that: (i) conflict induced by synchronous visuo-tactile stimulation in a body context is associated with a delayed conscious access compared to asynchronous visuo-tactile stimulation, (ii) this effect occurs only in the context of a visual body form, and (iii) is not due to detection or response biases. The results indicate that body-related visuo-tactile conflicts impact visual consciousness by facilitating access of non-conflicting visual information to awareness, and that these are sensitive to the visual context in which they are presented, highlighting the interplay between bodily signals and visual experience. Highlights: We studied the effects of visuo-tactile conflicts on visual awareness using CFS. Visual stimuli took longer to reach awareness during multisensory conflicts. This effect was only present in the context of a body form but not an object. Access to awareness is modulated by high level multisensory conflicts.